Exposure of animals and man to toluene. - Carlsson, Anders; Lindqvist, Thomas (Scandinavian Journal of Work, Environment & Health, 1977)
Twenty rats were exposed for 60 min to 14C-labeled toluene (1,950 mg/m3) in the inspired air. The largest amounts of toluene and its metabolites were found in the white adipose tissue. In a second series of experiments seven healthy male subjects were exposed to 375 mg/m3 of toluene in the air rest and during light, moderate and heavy physical exercise on a bicycle ergometer. The duration of each exposure period was 30 min. Of the seven male subjects three were thin, one was slightly overweight, and three were excessively overweight. The concentration of toluene in the alveolar air and the total uptake of toluene were determined during exposure. The thin subjects had a higher concentration of toluene in alveolar air than the other subjects both at rest and during exercise. The total uptake of toluene in the body during exposure showed that the subjects with the least amount of adipose tissue had the smallest uptake and the subjects with the largest amount of adipose tissue had the largest uptake.
Keywords: adipose tissue; alveolar air; animal; exposure; man; organ concentration; rat; toluene; uptake